Effectiveness of improving nutrition on depressive symptoms and work ability: Study protocol for the mind nutrition randomized controlled trial - Kipfer, Aino; Kahala, Minna; Kyhä, Henna; Nurmi, Cimmo; Puustinen, Juha; Korkeila, Jyrki; Ruusunen, Anu; Kunvik, Susanna (SAGE PUBLICATIONS INC, 2025)
Background: Depression is a growing public health concern that negatively impacts work ability and performance. Psychiatric nurses have an elevated risk for depressive symptoms, and it is essential to ensure their good mental health and work ability. The association between nutrition and depression is recognized, but there is a need for randomized, controlled intervention studies investigating the effectiveness of diet on depressive symptoms and related work impairment.
Aim: Mind Nutrition is a randomized, controlled intervention study examining whether improving nutrition can reduce depressive symptoms and depressive symptoms-related sick leaves and enhance work ability and quality of life among mental health and substance abuse professionals.
Methods: We will recruit 125 nurses and social welfare professionals from the mental health and substance abuse field of the Satakunta Wellbeing Services County. Half of the participants will be randomized to the intervention and half to the control group. Subjects in the intervention group will participate in two individual and three group counselling sessions during a 6-month intervention. Nutrition counselling follows the Finnish Nutrition Recommendations. The control group will maintain their habitual diet. The Center for Epidemiological Studies - Depression, depressive symptoms-related sick leave days, two work ability indicators, a Food Frequency Questionnaire, three-day food records, Three-Factor Eating Questionnaire - 18 and WHO-8 Eurohis Quality of Life will be assessed at baseline and 6 months.
Summary: This study will provide evidence of the effectiveness of nutrition counselling on depressive symptoms and related sick leave days, work ability and quality of life.